Interaction Between Consumers and Emerging Forms of Artificial Intelligence: a Discriminant Analysis - Pelău, Corina; Ene, Irina (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
The interaction between consumers and companies has been changed because of the development and implementation of artificial intelligence. On one hand, the implementation of artificial intelligence systems increases the efficiency and rapidity of certain processes, by making the life of consumers and companies easier. On the other hand, their implementation brings certain challenges because of the changes it involves, including the acceptance of artificial intelligence systems by the consumers, the ability to learn how to operate the robots as well as the protection of the information gathered by these systems. In this paper, we aim to measure the acceptance of consumers regarding different forms of artificial intelligence systems. By applying a discriminant analysis, we measure the preference of consumers towards human versus robot interaction as well as between different types of robots with different forms and degrees of anthropomorphic characteristics. The results show that consumers prefer human interaction to the interaction with robots, especially in cases where they are not familiar with the robot interaction. Besides, they prefer the communication to classic robots in comparison to human holograms and they have a certain curiosity towards humanoid robots in opposition to classic robots.